2019
DOI: 10.1590/1809-2950/17027326042019
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aquatic and treadmill exercise in individuals with chronic stroke

Abstract: We compared the effect of gait training on treadmill versus deep water on balance and gait in 12 ischemic stroke chronic survivors randomly sorted to the Pool or Treadmill Groups. Berg Scale (BBS) and timed up and go test (TUG) were applied before and after the interventions. Just one person applied all tests and she was blinded for the aims of the study. Surface EMG of the paretic and non-paretic (NP) side muscles were recorded during walking on a treadmill. Three 100-ms epochs were extracted from the EMG rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Overall, 148 studies and 5987 patients with stroke were included in this meta‐regression analysis. 6 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ,…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 148 studies and 5987 patients with stroke were included in this meta‐regression analysis. 6 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ,…”
Section: Resultsmentioning
confidence: 99%
“…Franciulli [21] applied an intervention lasting 9 weeks, divided into a group that performed aerobic training (walking on the ground, treadmill and relaxation) and the other aerobic training in water, in which both interventions positively affected the TUG scores and BBS. A recent meta-analysis by Veldema and Jansen [36] demonstrated that aquatic therapy has superior efficacy in balance, walking, muscle strength, proprioception, health-related quality of life, physiological indicators, and cardiorespiratory fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the evaluative tools, most of the studies included for synthesis more than one instrument to assess balance and functional capacity. The BBS was present in 10 of the 14 articles [17][18][19][20][21][22][23][24][25][26], as it is an easy and quick scale to apply, in addition to having high reliability [27], followed by the TUG which was present in 8 of the 14 articles [21][22][23][24][25][26]28,29], as it is a reliable, valid and easy-to-administer clinical tool to assess advanced functional mobility after a CVA [30].…”
Section: Discussionmentioning
confidence: 99%